Profile of weekly training load in elite male professional basketball players - Manzi, V.; D'Ottavio, S.; Impellizzeri, F. M.; Chaouachi, A.; Chamari, K.; Castagna, C. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to examine the training load (TL) profile of professional elite level basketball players during the crucial parts of the competitive season (pre-play-off finals). Subjects were 8 full-time professional basketball players (age 28 ± 3.6 years, height 199 ±7.2 cm, body mass 102 ± 11.5 kg, and body fat 10.4 ± 1.5%) whose heart rate (HR) was recorded during each training session and their individual response to TL monitored using the session-rate of perceived exertion (RPE) method (200 training sessions). The association between the session-RPE method and training HR was used to assess the population validity of the session-RPE method. Significant relationships were observed between individual session-RPE and all individual HR-based TL (r values from 0.69 to 0.85; p < 0.001). Coaches spontaneously provided a tapering phase during the competitive weeks irrespective of the number of games played during it (i.e., 1 or 2 games). The individual weekly players' TL resulted in being not significantly different from each other (p > 0.05). Elite male professional basketball imposes great physiological and psychological stress on players through training sessions and official competitions (1-2 per week). Consequently, the importance of a practical and valid method to assess individual TL is warranted. In this research, we demonstrated that session-RPE may be considered as a viable method to asses TL without the use of more sophisticated tools (i.e., HR monitors). The session-RPE method enabled the detection of periodization patterns in weekly planning in elite professional basketball during the crucial part of the competitive season (1 vs. 2 weekly fixtures model).